In Silico Study: Metabolite Compounds of Zingiber Officinale Var. Rubrum as Potential E2F2 Inhibitor Agents in Breast Cancer Signaling Pathway - Khoirunnisa Purwamita Budiutami; Aryo Tedjo; Fadilah Fadilah; Surya Dwira; Ajeng M. Fajrin (Eduvest - Journal of Universal Studies, 2026)
Breast cancer ranks among the leading causes of death in women, linked to disruptions in signaling pathways regulating cell proliferation and survival, particularly E2F2 gene activity. E2F2 regulation falters when pRB is phosphorylated by Cyclin D–CDK4/6 or Cyclin E–CDK2 complexes, freeing E2F2 to activate cell cycle genes. This study, "In Silico Study: Metabolite Compounds of Zingiber officinale var. rubrum as Potential E2F2 Inhibitor Agents in Breast Cancer Signaling Pathway," assesses red ginger (Zingiber officinale var. rubrum) metabolites as CDK4/CDK6 inhibitors via molecular docking in silico. Target protein structures came from the Protein Data Bank; metabolites were chosen for reported anticancer effects and 3D-modeled. Docking used Molegro Virtual Docker to gauge ligand affinity and interactions at active sites. Results highlighted [12]-shogaol, (E,E)-α-farnesene, and 1-dehydro-[6]-gingerdione as CDK4 inhibitors; azafrin, [8]-shogaol, and [12]-shogaol for CDK6. These exhibit strong binding via hydrogen bonds and hydrophobic interactions at key residues. Red ginger metabolites show promise as CDK4/CDK6 inhibitors for breast cancer therapy, pending in vitro/in vivo validation.